Canada. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Canada during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as resilience against climate change, plant health, animal health, research, export, methodologies, innovation, trade inside and outside. Likewise, support was given to genetic improvement and food processing. Finally, work was done on the fruit and cocoa value chain.